Recurrent Kawasaki disease at a tertiary care center in Chandigarh, North West India: 24 years of clinical experience. (3rd March 2019) - Guleria, Sandesh; Pilania, Rakesh Kumar; Jindal, Ankur Kumar; Bhattarai, Dharmagat; Suri, Deepti; Singh, Surjit
Abstract: Background: Kawasaki disease (KD) is emerging as the most common medium vessel vasculitis in children. Recurrence of KD (0.8%‐3.0%) is unusual and not commonly reported. Objective: To study the clinico‐laboratory profile of children with recurrent KD. Methods: Case records of 714 children with KD, registered from January 1994 to April 2018 in the Pediatric Rheumatology Clinic at the Advanced Pediatrics Centre, Post Graduate Institute of Medical Education and Research Chandigarh, were reviewed and data were analyzed for children having had recurrent KD. Results: Seven (0.98%) children (five boys; two girls) had recurrent KD in our cohort of 714 patients. Mean age at diagnosis was 4.3 years (range, 2‐9 years). Six (85.7%) had recurrence of KD within 1.5 years. Incomplete KD was more common during recurrence (71.4%) as compared to the first episode (33.3%). Five children with recurrent KD developed desquamation during the first week of illness. Laboratory investigations did not show any significant difference during the two episodes of KD. Six of the seven children in the first episode received treatment with intravenous immunoglobulin (IVIG). Five of the seven children received IVIG during recurrence. One child had transient left main coronary artery ectasia during the first episode of KD as well as during recurrence and it normalized after treatment on both occasions. Conclusion: Recurrences in KD are unusual. Over a period of 24 years the recurrence rate in our cohort of children with KD was 0.98%. Further, children with recurrences tended to have milder and incomplete form of the disease.